Patterns of Google search behavior for multiple sclerosis in the Philippines: An infodemiological study - Kurt Joshua E Baladjay; Roland Dominic G Jamora (Digital Health)
Background Multiple sclerosis (MS) is a chronic autoimmune disease caused by demyelination in the central nervous system primarily affecting younger adults leading to disability due to sensorimotor deficits and cognitive impairment. Online search volume index (SVI) can be used as a surrogate marker to explore interest and awareness for MS in the Philippines. Objectives This study aimed to describe the online searching behavior and interest for MS in the Philippines and explored its implications in the current healthcare situation surrounding the disease in the country. Methods Using Google Trends, the monthly SVI for the term “Multiple Sclerosis” from 1 January 2014 to 31 July 2024 in the Philippines was determined and its related queries. Philippine data was compared with worldwide data by using Spearman rank correlation, and MS SVI was compared with top neurologic diseases in the Philippines. Results The SVI for MS generally remained in the same level over the last 10 years, with only two peaks, and no seasonal or annual variation observed. Worldwide SVI trends did not correlate with Philippine SVI trends. SVI for MS ranked the lowest in comparison to the top four neurologic diseases in the Philippines. Conclusion SVI trends of MS in the Philippines mirrored its prevalence and incidence, current state of healthcare delivery, and research productivity in the country. This signals opportunities to increase awareness for MS and capacity of the healthcare system to adequately diagnose and treat said disease entity.